The combining ability of extra-early maturing quality protein maize (Zea mays) inbred lines and the performance of their hybrids in Striga-infested and low-nitrogen environments - Okunlola, Gbemisola; Badu-Apraku, Baffour; Ariyo, Omolayo; Ayo-Vaughan, Moninuola (Frontiers in Sustainable Food Systems, 2023)
Maize production in sub-Saharan Africa (SSA) faces challenges due to the damage caused by the parasitic weed, Striga hermonthica (Del.) Benths and low soil nitrogen. To address these constraints and improve food security and nutrition, this study assessed the combining ability of 47 inbred lines and four testers, grouped them into heterotic groups, identified effective testers, and determined the stability of the lines in hybrid combinations under contrasting research conditions. The study was conducted at Mokwa and Abuja during the 2019 and 2020 growing seasons. One hundred and ninety-six hybrids comprising 188 testcrosses, 6 hybrids derived by intermating the four testers, and two commercial checks were evaluated using a 14 × 14 lattice design with two replicates. Results revealed that under Striga infestation, the best quality protein maize (QPM) hybrid, TZEEQI 468 × TZEEQI 321, outyielded the best check, TZEEQI 342 × TZEEQI 7, by 24%. Under low-N, QPM hybrid, TZEEQI 515 × TZEEQI 321 outyielded the best check, TZEEQI 507 × TZEEQI 7 by 11% while under optimal conditions the best QPM hybrid, TZEEQI 506 × TZEEQI 321 outyielded the best check, TZEEQI 342 × TZEEQI 7 by 2%. General combining ability (GCA) and specific combining ability (SCA) significantly influenced grain yield and other measured traits across the test environments. These indicated the importance of both additive and non-additive genetic variances in trait inheritance. GCA was more important than SCA for grain yield and most traits in contrasting environments. Four inbred lines had significant and positive GCA effects for grain yield under Striga-infested conditions, while three lines had similar GCA effects under low-nitrogen conditions. These lines demonstrated outstanding potential for developing Striga-resistant and low-nitrogen-tolerant hybrids. The study identified four heterotic groups using the heterotic grouping method based on the general combining ability of multiple traits (HGCMAT). Inbred lines TZEEQI 490 and TZEEQI 460 were identified as testers. The QPM hybrid TZEEQI 515 × TZEEQI 321 exhibited outstanding yield and stability across contrasting environments, highlighting the need for extensive on-farm trials to confirm its superiority and potential for commercialization in SSA.